THE ANALYSIS CHEMICAL COMPOSITION OF CATFISH HEADFLOUR (Clariasgariepinus) - Widiyanto, Rifki Rahma; Karnila, Rahman; Ilza, Mirna (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aimed to determine the chemical content of catfish head flour catfish (Clariasgariepinus).The research was conducted in two stages, those were the preparation of catfish head flour and then the proximate analysis of catfish head flour.The parameters used in first step were the percentage of body parts and yield, while those in the second stage werethe content ofmoisture, ash, protein, fat, and carbohydrate. The results showed that the whole catfish was consisted of head 29.73%, visceral 6.63%, and meat 63.64%.The yield of catfish head flour was 39.74%. Its chemical composition was consisting of the moisture 9.62% (wet based), ash17.25% protein 50.94%, fat 19.66%, and carbohydrate 4.94%(dry based). Keywords :Clariasgariepinus, flour, proximate, yield